The Role of eIF4G-1 Isoforms and Live Cell Imaging of IRES-mediated Translation Initiation in Breast Cancer Cells - Crosson, Whitney K. (East Carolina University, 2012)
The development of cancer is a consequence of mutations that lead to dysfunctional cell processes such as unrestrained cell proliferation, resistance to apoptosis, and improper regulation of cell processes such as translation. Cell proliferation and apoptosis are linked to specific gene expression events regulated by protein synthesis, which begins with the binding of various eukaryotic initiation factors (eIF) to mRNA and ribosomes to initiate translation. eIF4G-1 catalyzes two types of translation initiation. Cap-dependent translation requires eIF4E to bind a 5'-methylated mRNA cap and eIF4G-1. This in turn facilitates recruitment and promotes translation of cell cycle and growth-related proteins. Cap-independent translation initiates internally through internal ribosome entry sites (IRES) in the 5' UTR of mRNA and promotes translation of apoptotic mRNAs such as Apaf-1. Previous studies found that eight variants of eIF4G-1 mRNA exist, and five protein isoforms can be resolved by electrophoresis. Each isoform may potentially form a translation complex with activities that differ slightly based on modular binding sites. We hypothesized that the representation of eIF4G-1 isoforms and their activity in the initiation complex varies in tumor-forming human breast cell lines vs. non-tumor-forming lines. However, when eIF4G-1 isoform representation was determined in three breast carcinoma cell lines and one non-tumorigenic breast epithelium cell line, no such systematic increase or decrease of individual isoforms was found. Similar results were seen after two breast cancer cell lines were treated with the chemotherapeutic reagents etoposide and cisplatin. Previous studies in our laboratory demonstrated that in population of human breast cancer cells cap-independent translation could be induced as indicated by the use Apaf-1 IRES, suggesting a shift towards pro-apoptotic protein synthesis. We have now developed a novel dual fluorescence bicistronic reporter containing either the Apaf-1 IRES, or a viral IRES to assay the propensity of these cells on an individual cell basis toward cap-independent translation in vivo. Our results confirm the ability of this assay to measure the ratio of cap-dependent versus cap-independent initiation in single live cells as demonstrated by blue fluorescence or green fluorescence, respectively. By establishing the role of eIF4G-1 isoforms in pro-apoptotic protein synthesis, it may be possible to direct a cell from proliferation to apoptosis by targeting certain isoforms.
Keywords: Chemistry, Biochemistry; Biology, Cellular; Biology, Molecular; EIF4G; Live-cell imaging; Molecular biology; Cellular biology; Biochemistry; Breast--Cancer--Research; Cell proliferation; Apoptosis; Cellular control mechanisms